Jan Åge Riseth; Sámi reindeer management under technological change 1960-1990: Implications for Common-Pool Resource Use Under Various Natural and Instututional Conditions. A comparative analysis of regional development paths. - Haugerud (ed.), Rolf Egil (Rangifer, 2000)
On June 22, Cand. Agric. Jan Åge Riseth successfully defended his dissertation "Sami reindeer management under technological change 1960-1990: Implications for Common-Pool Resource Use Under Various Natural And Institutional Conditions. A comparative analysis of regional development paths in West Finnmark, North Trøndelag, and South Trøndelag/Hedmark, Norway." for the degree Dr. Scient, at the Agricultural University of Norway (AUN), Dept. of Economics and Social Sciences.